VLA-1 Binding to Collagen IV Controls Effector T Cell Suppression by Myeloid-Derived Suppressor Cells in the Splenic Red Pulp - Eckert, Ina N.; Ribechini, Eliana; Jarick, Katja J.; Strozniak, Sandra; Potter, Sarah J.; Beilhack, Andreas; Lutz, Manfred B. (Frontiers in Immunology, 2021)
Myeloid-derived suppressor cells (MDSCs) represent a major population controlling T cell immune responses. However, little is known about their molecular requirements for homing and T cell interaction to mediate suppression. Here, we investigated the functional role of the homing and collagen IV receptor VLA-1 (a1b1-integrin) on in vitro GM-CSF generated murine MDSCs from wild-type (WT) and CD49a/a1-integrin (Itga1-/-) gene-deficient mice. Here, we found that effector (Teff) but not naive (Tn) CD4+ T cells express VLA-1 and monocytes further up-regulated their expression after culture in GM-CSF when they differentiated into the monocytic subset of resting MDSCs (R-MDSCs). Subsequent activation of R-MDSCs by LPS+IFN-g (A-MDSCs) showed increased in vitro suppressor potential, which was independent of VLA-1. Surprisingly, VLA-1 deficiency did not influence A-MDSC motility or migration on collagen IV in vitro. However, interaction times of Itga1-/- A-MDSCs with Teff were shorter than with WT A-MDSCs on collagen IV but not on fibronectin substrate in vitro. After injection, A-MDSCs homed to the splenic red pulp where they co-localized with Teff and showed immediate suppression already after 6h as shown by inhibition of T cell proliferation and induction of apoptosis. Injection of A-MDSCs from Itga1-/- mice showed equivalent homing into the spleen but a reduced suppressive effect. Interaction studies of A-MDSCs with Teff in the subcapsular red pulp with intravital 2-photon microscopy revealed also here that MDSC motility and migration parameters were not altered by VLA-1 deficiency, but the interaction times with Teff were reduced. Together, our data point to a new role of VLA-1 adhesion to collagen IV as a prerequisite for extended contact times with Teff required for suppression.